2014
DOI: 10.1063/1.4883183
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relation between oxygen vacancies and ferromagnetism in Fe-doped TiO2 nano-powders

Abstract: In this work, we present an experimental and theoretical study of structural and magnetic properties of Fe doped rutile TiO2 nanopowders. We show that Fe-doping induces the formation of oxygen vacancies in the first-sphere coordination of iron ions, which are in +2 and +3 oxidation states. We found that Fe ions form dimers that share one oxygen vacancy in the case of Fe3+ and two oxygen vacancies in the case of Fe2+. The saturation magnetization is almost independent of iron concentration and slightly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
2
14
1
Order By: Relevance
“…The lower H c values exclude the possibility of segregation of a metallic Fe phase 16. In addition, M s seems to be independent of the iron concentration, that is, only a small part of the total volume of the sample is related to the ferromagnetic contribution of the system 14. The M s value obtained in this study (ca.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations
“…The lower H c values exclude the possibility of segregation of a metallic Fe phase 16. In addition, M s seems to be independent of the iron concentration, that is, only a small part of the total volume of the sample is related to the ferromagnetic contribution of the system 14. The M s value obtained in this study (ca.…”
Section: Resultsmentioning
confidence: 44%
“…Figure 2 shows the temperature dependence of the susceptibility for 57 Fe‐TiO 2 and 57 Fe‐Sn‐TiO 2 . The curves for samples with different iron concentrations show a temperature dependence similar to that expected for a pure paramagnet, but they do not tend to zero at high temperatures, and thus indicate the presence of a fraction of ions in a magnetically ordered phase 14. Doubtless, doping of Fe 3+ ions into the TiO 2 lattice leads to the formation of oxygen vacancies to maintain the charge balance, and the higher the degree of Fe doping, the higher the concentration of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…They reported sharp ferromagnetic to paramagnetic transition with a high Curie temperature (T c ) ≈793 K for 3% Co‐doped TiO 2 NPs. Navarro et al showed that Fe‐doped rutile TiO 2 samples have ferromagnetic, paramagnetic, and antiferromagnetic contributions . They suggested that the ferromagnetism in Fe‐doped rutile TiO 2 strongly depends on defects.…”
Section: Introductionmentioning
confidence: 99%